Industry Partnerships as a Strategy for Enhancing Learning Innovation and Vocational School Branding - Muhammad Nuruzzaman; Tony Wijaya; V. Lilik Hariyanto; Aan Yudianto (Jurnal Pendidikan Teknik Sipil, 2026)
Background: Collaborations between schools and industry are often merely formalized without a deeper understanding of their benefits. This study will examine the benefits of industry partnerships from the perspective of learning innovation and vocational school branding. Method: The research method used is qualitative with a phenomenological approach. Two schools with unique furniture specialties will be selected. Six respondents will be selected from each school. Data collection will be conducted using primary data (in-depth interviews and participant observation) and secondary data (supporting documents). Result: The results showed that the benefits of partnerships from the perspective of learning innovation are the implementation of TEFA and industry participation in the implementation of the Final Project. Meanwhile, from the perspective of vocational school branding, industry can assist schools in providing positive branding to the community. Conclusion: School-industry partnerships offer numerous benefits in various areas. This collaboration needs to be maximized to benefit learning innovation, school branding, and other sectors.